DETERMINING PEDAGOGIC AND PROFESSIONAL COMPETENCIES AMONG STUDENTS IN REALIZING SOCIETY 5.0 (JURNAL ECONOMICA : Research of Economic And Economic Education, 2019)
The application of information technology is very useful in improving teaching skills and content development.. The magnitude and pace of information in society influences the variation, depth and complexity of education and learning studies. This paper’s aim is to conduct a critical analysis of technological empowerment in the development of pedagogical and professional competencies as prospective professional teachers. The study was conducted with a qualitative approach among students in the economic education study program, FKIP, Satya Wacana Christian University, Salatiga, Indonesia. Data collection techniques are carried out by interviews, observation and focus group discussion. Sources of research data include students, administrators of student associations, and lecturers. The research found that students have applied information technology for college administration, found learning resources, published lectures, business and social media.that the students had applied information technology to lecture administration, found learning resources, published lectures, business and social media. Artificial intelligence is formed by looking for content, opportunities, and self-development networks. More specifically, students explain that unlimited access provides easy learning about how to teach (pedagogically) and deepen the theory of the economy (professional). The path of academic and social communication develops on line and reaches out to objects that are relevant to their studies. Meanwhile, the lecturers recommend that students need to be facilitated by broad access, to facilitate students in information technology applications.